The integration of CSR management systems and their influence on the performance of technology companies - Juan Andrés Bernal-Conesa; Antonio Juan Briones-Pe\~nalver; Carmen de Nieves-Nieto (European Journal of Management and Business Economics (EJM&BE), 2016)
This paper proposes a model in order to analyze whether standardized management systems facilitate the implementation and integration of CSR within the technology company, studying which is the influence of CSR in reputation and improvement of these companies and whether it has a positive impact on the economic performance of the company. The study was conducted in companies located in Spanish Science and Technology Parks. On the one hand, model results shows that there is a positive, direct and statistically significant relationship between the integration of CSR and reputation; on the other hand, performance and internal improvement has also this relationship. Likewise, the model shows also some indirect relations between management system before the implementation of CSR and reputation and internal improvement.
Keywords: M14; 650; Corporate Social Responsibility; Improvement and reputation; Integration; Technology companies